Integration of Ecomuseum and Living History: An Educational Space Concept Based on Local Wisdom and Past Culture - Nining Winarsih (Biokultur, 2026)
Conventionally, museums are positioned as enclosed spaces for preserving cultural heritage, characterized by formal and informative interactions between staff and visitors. This concept emphasizes preservation and documentation functions but has not fully provided participatory and contextual educational experiences for the public. This study aims to analyze the integration of the ecomuseum and living history concepts as an educational model focusing on the environment, local wisdom, and past cultural practices, which can enhance visitor participation and ecological awareness. The research employed a qualitative approach using observation, literature review, and in-depth interviews with museum managers, cultural communities, and visitors. Data were analyzed through thematic analysis to identify patterns of meaning from experiences and practices implemented in the development of green, past-themed museums. The findings indicate that the combination of green open spaces, traditional food, classic clothing, and historical narratives delivered by guides and museum staff can strengthen environmental literacy, enhance immersive experiences, and deepen the understanding of local culture. Theoretical frameworks applied include ecopedagogy, Bandura’s social learning theory, and the local wisdom approach in education, which collectively explain the effectiveness of this integrative model. The study recommends the adoption of the eco-living museum concept in museum management and educational policies to create environmentally friendly, participatory, and sustainable learning spaces.